ANALISIS PENERIMAAN DAN DISTRIBUSI LOGISTIK PADA PEMILU 2019 DI KOMISI PEMILIHAN UMUM KABUPATEN MAMBERAMO TENGAH - Dian Maya Septyaningtias; Septinus Saa; Renida J Torobi (Universitas Cenderawasih, 2023)
The purpose of this study is to explain and analyze the 2019 election logistics distribution process in Central Mamberamo District, analyze the factors that support and hinder the logistics distribution process, and propose efforts that need to be made to improve the quality of the election logistics distribution in Central Mamberamo district. The method used is the descriptive qualitative research method. Data collection techniques used in this study were in-depth interviews, active observation, and FGD (Focus Guide Discussion). The steps taken to analyze the data that have been obtained from the results of literature studies, observations, and interviews are to analyze in more detail by coding the data, restating themes and descriptions in narrative form, and interpreting research results with information derived from literature studies. or theory. The results of research on the distribution of election logistics in 2019 in Central Mamberamo Regency are that the distribution of logistics in the 2019 elections in Central Mamberamo Regency has two main focuses, namely the distribution process from third parties or tender winners to the KPU and distribution of post-packaging logistics. The factors that support and hinder the logistics distribution process for the 2019 Election in Central Mamberamo Regency are support in logistics distribution, namely the implementing human resources, distribution facilities, and infrastructure.